Creating Legitimacy for Citizen Initiatives: Representation, Identity and Strategic Networking. (26th May 2020) - Connelly, Steve; Bryant, Margi; Sharp, Liz
ABSTRACT: Citizen-led initiatives raise practical and theoretical questions about the criteria by which their democratic legitimacy should be judged.  While existing analytical and normative frameworks are problematically based on a `state'/`citizen' binary, a network ontology which sees these as strategically-deployed constructs is more practically adequate for analysis. We demonstrate this through a case of a successful citizen initiative, and conclude that such analysis should examine processes of strategic networking, along with claims and constructions of representation and identity.  This means not taking participants' categories, identities, and evaluations for granted, and privileging the possibility of challenge as a fundamental democratic criterion.